Between food and spectacle: The complex reconfigurations of rural production in agritourism. Issue 126 (November 2021) - Montefrio, Marvin Joseph F.; Sin, Harng Luh
Highlights: Agritourism in the Philippines tends towards production of spectacle. Production of spectacle serves urbanite imaginations of the rural. Spectacle can disrupt, redefine, and curtail on-site food production. Spectacle's impact on food production can extend beyond the farm gate. Agritourism's emphasis on spectacle questions its food security potential. Abstract: Agritourism has often been framed as a means to revitalize a declining rural economy by improving and diversifying household incomes, forestalling rural flight, and preserving agrarian cultures. We argue, however, that it can also have the propensity to create a different kind of rural revitalization, one that accentuates the production of spectacle, at times at the expense of food production. We draw from qualitative field research to examine the growing agritourism movement in the Philippines, a country with a struggling rural sector. We observe that agritourism sites in the Philippines negotiate space and work in multiple ways and highlight the tensions that farmers increasingly perceive on the ground. Some farmers persist in maintaining the production of food, while others shift more towards the staging of experience and spectacle to serve urbanite imaginations of the rural. We present various tendencies in the process of transitioning from farm to agritourism and argue that attention to the production of rural spectacle is important in understanding agrarian transitions at the farm and community level, and ultimately agritourism's implications on rural revitalization.